Progress in scale up of HIV viral load testing in select sub-Saharan African countries 2016-2018. - Peter N Fonjungo; Shirley Lecher; Clement Zeh; Erin Rottinghaus; Helen Chun; Christiane Adje-Toure; Spencer Lloyd; Jane W Mwangi; Michael Mwasekaga; Yohannes Mengistu Eshete; Rituparna Pati; Tsietso Mots'oane; et al. (PLoS ONE, 2023)
Introduction We assessed progress in HIV viral load (VL) scale up across seven sub-Saharan African (SSA) countries and discussed challenges and strategies for improving VL coverage among patients on anti-retroviral therapy (ART). Methods A retrospective review of VL testing was conducted in Côte d'Ivoire, Kenya, Lesotho, Malawi, Namibia, Tanzania, and Uganda from January 2016 through June 2018. Data were collected and included the cumulative number of ART patients, number of patients with ≥ 1 VL test result (within the preceding 12 months), the percent of VL test results indicating viral suppression, and the mean turnaround time for VL testing. Results Between 2016 and 2018, the proportion of PLHIV on ART in all 7 countries increased (range 5.7%-50.2%). During the same time period, the cumulative number of patients with one or more VL test increased from 22,996 to 917,980. Overall, viral suppression rates exceeded 85% for all countries except for Côte d'Ivoire at 78% by June 2018. Reported turnaround times for VL testing results improved in 5 out of 7 countries by between 5.4 days and 27.5 days. Conclusions These data demonstrate that remarkable progress has been made in the scale-up of HIV VL testing in the seven SSA countries.